Bio-functionalized nickel-silica nanoparticles suppress bacterial leaf blight disease in rice (Oryza sativa L.) - Abdallah, Yasmine; Nehela, Yasser; Ogunyemi, Solabomi Olaitan; Ijaz, Munazza; Ahmed, Temoor; Elashmony, Ranya; Alkhalifah, Dalal Hussien M.; Hozzein, Wael N.; Xu, Lihui; Yan, Chengqi; Chen, Jianping; Li, Bin (Frontiers in Plant Science, 2023)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most devastative diseases that threatens rice plants worldwide. Biosynthesized nanoparticle composite compounds have attracted attention as environmentally safe materials that possess antibacterial activity that could be used in managing plant diseases. During this study, a nanocomposite of two important elements; nickel and silicon, was biosynthesized using extraction of saffron stigmas (Crocus sativus L.). Characterization of obtained nickel-silicon dioxide (Ni-SiO2) nanocomposite was investigated using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Transmission/Scanning electron microscopy (TEM/SEM), and Energy dispersive spectrum (EDS). Antibacterial activities of the biosynthesized Ni-SiO2 nanocomposite against Xoo were tested by measuring bacterial growth, biofilm formation, and dead Xoo cells. The bacterial growth (OD600) and biofilm formation (OD570) of Xoo treated with distilled water (control) was found to be 1.21 and 1.11, respectively. Treatment with Ni-SiO2 NPs composite, respectively, reduced the growth and biofilm formation by 89.07 and 80.40% at 200 μg/ml. The impact of obtained Ni-SiO2 nanocomposite at a concentration of 200 μg/ml was assayed on infected rice plants. Treatment of rice seedlings with Ni-SiO2 NPs composite only had a plant height of 64.8 cm while seedlings treated with distilled water reached a height of 45.20 cm. Notably, Xoo-infected seedlings treated with Ni-SiO2 NPs composite had a plant height of 57.10 cm. Furthermore, Ni-SiO2 NPs composite sprayed on inoculated seedlings had a decrease in disease leaf area from 43.83% in non-treated infected seedlings to 13.06% in treated seedlings. The FTIR spectra of biosynthesized Ni-SiO2 nanocomposite using saffron stigma extract showed different bands at 3406, 1643, 1103, 600, and 470 cm-1. No impurities were found in the synthesized composite. Spherically shaped nanoparticles (NPs) were observed by using TEM, and SEM. EDS revealed that Ni-SiO2 NPs have 13.26% Ni, 29.62% Si, and 57.11% O. Xoo treated with 200 µg/ml of Ni-SiO2 NPs composite drastically increased the apoptosis of bacterial cells to 99.61% in comparison to 2.23% recorded for the control. The application of Ni-SiO2 NPs significantly improved the vitality of rice plants and reduced the severity of BLB.